An investigation into the knowledge management practices and challenges in an international non-governmental network of organisations : a case study of One World International - Lumba, Patricia Mweene Haamujompa (Library and Information Studies Centre (LISC), 2024)
Knowledge management will support activities that improve the performance of organizations and organization networks due to the known benefits of collaborating. Although knowledge management is deemed to be vital for organizations, no uniform model of practice exists for any organization. This condition can also be ascribed to the scarcity of information on Knowledge management practices, experiences, role models and general concerns. Concerns of the critical role knowledge management can play in NGOs, including NGO networks; due to their complex structures have often been addressed. These concerns include among others the priority given to external action and the client versus internal administration work and results analysis; structural high turnover among staff, volunteers and donors; the lightness of the permanent structure and the performance of field activities in a situation and climate of emergency and orllack of funds, and/or in stressed or disorganized environments. This report is based on the outcomes of a study that explored the knowledge management practices and challenges in an international NGO network; OneWorld International (OWl). The investigation constituted comparative case studies of two centres (one in Zambia and the other in the Netherlands) belonging to a single international network. An empirically grpunded framework of knowledge management practices based on the taxonomy proposed by Holsapple and Joshi was utilised as the reference framework for the study. The framework provided guidelines to characterize factors that influence organizational knowledge management; knowledge manipulation activities (processes) and organizational knowledge resources. The study uses two approaches: qualitative and quantitative. The qualitative approach, which was used in the preliminaiy stage of the data collection exercise, provided an in-depth interpretation by means of open-ended interviewing of the knowledge management issues that needed to be grasped. The qualitative approach was complemented by a quantitative approach using a Likert scale based on attitude statements. The attitude statements were developed from the responses obtained during the open interviews. The quantitative approach also provided the means to make comparisons between the centres and provided the results of opinions, beliefs and attitudes of the respondent's knowledge management perceptions. The results of the empirical study confirm that a variety of factors affect knowledge management behaviours in NGO networks. These factors include managerial and internal controls such as management styles and incentives for knowledge creation and sharing; resource influences; and environbental influences relating to an organization's culture and the needs of partner organizations. The study highlights important variation in diversity, gaps and perceptions in managing knowledge between centres in the network that are based in Europe and Africa. This is despite significant commonality in knowledge management processes and infrastructures. The results further show that institutionalisation of knowledge management practices within a network seem to enable or constrain knowledge management at centre and network level. Recommendations are proposed to improve knowledge management practices at local and international level and include enhanced technical and advisory services at international level; capacity building; creating greater awareness of knowledge management; decentralization of knowledge management processes; implementation of a knowledge management strategy at network level and improving relationships between centres. The research concludes that networked NGOs and specifically OWl could operate more efficiently and incrementally enhance service provision by leveraging their knowledge resources more effectively. It is in this light that knowledge management practices should be examined in NGOs and particularly networks with their complex structures and attendant reoccurring and unavoidable problems.